Study on modified curve fitting model in analyzing YIG resonator antenna. Issue 2 (21st December 2018) - Othman, Mohamadariff; Wan Ali, Wan Fahmin Faiz; Ain, Mohd Fadzil; Ahmad, Zainal Arifin; Wan Mohd Mahiyiddin, Wan Amirul; Qasaymeh, Yazeed
Abstract: In this study, a modified curve fitting model (CFM) for cylindrical dielectric resonator antenna (DRA) exclusively using YIG resonator with excess Fe2 O3 is proposed. The modified CFM is used to accelerate the analysis of YIG resonator antenna (YRA) without having to repeat the characterization process for similar resonator. Modification of CFM is done using least square method in which correlation and regression analyses are used. The modified equations of resonant frequency and Q‐factor are adapted for the YRA design using YIG resonator with excess Fe2 O3 of 9%. Comparison between the simulation, measurement, and modified CFM results are very well matched.